Ai-powered education: Unlocking a world of possibilities - GÜSAN KÖSE, GÖZDE; EMRE, İLKİM ECEM (My University, 2023)
Introduction: With the help of recent advances in artificial intelligence (AI) and applications based on AI technologies, education has become one the most affected areas in life. Especially, Although, the staff members and students may not have a comprehensive perception of the usage of AI properly, in the near future, this topic may be needed to be discussed in detail among universities’ administrative level. In higher education, AI applications could serve for many purposes, both for academic and administrative work, also for students. There are many questions to be answered and worth researching to measure different groups’ ability to adapt or readiness to use these technologies as well as awareness about these technologies. Therefore, it is important to understand how to adapt these AI applications in higher education, how to behave responsibly and how to gain the most advantages by the usage of these. Aim: The aim of this study is to have an understanding about academic and administrative staff members’ and students' awareness, perception and experience about AI technologies in higher education in Turkey. Additionally, it is aimed to discuss the challenges of ethical considerations related to the use of ChatGPT. The following research questions are hence the focus of the current study: RQ1:How aware are the academic and administrative staff and students about usage of AI applications? RQ2:How does the adoption of ChatGPT affect traditional teaching, studying and working conditions? RQ3:How does the usage of ChatGPT impact the learning outcomes of students? RQ4:What are the implications of integrating ChatGPT into academic research for both students and academic staff? RQ5:Which ethical issues should be considered while using ChatGPT in academia and and business processes? Methods: In the scope of the study, a pilot study will be conducted amongst administrative and academic staff members as well as students. These participants will be selected from Marmara University, Faculty of Business Administration. Sample will include academic staff members and students from business administration and management information system programs. Administrative staff members will be selected from personnel working in the faculty. Purposive and simple random sampling methods will be used for participant selection. The present study will follow a qualitative research design. Therefore, a structured interview will be used for data collection. The interview questions will consist both closed and open-ended questions about their awareness, perception and experience using ChatGPT, including any potential benefits the participants have encountered, how they have incorporated the model into their work/study and their ideas about ethical considerations. Discussion and Conclusion: The findings of our pilot study will be presented in this section. In addition, it is planned to expand the scope of this study by using these findings as an example to identify the factors to be used in another study (a quantitative research design). These findings would lead to a more comprehensive study in which number of participants are planned to be increased, students from different departments and universities are planned to be included to the sample. Moreover, in future studies, perceptions of academic staff members, administrative staff members and students could be examined in a more detailed way, which would be only possible to conduct studies only by focusing on one group.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim Bilişim Sistemleri; Social Sciences and Humanities; Management; Management Information Systems; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; AI; ChatGPT; higher education